Gender Differences in Critical Thinking through RADEC, Problem-based Learning, and Direct Instruction Learning Models - Dadan Setiawan; Ari Yanto; Siti Nurhalimah (Elementary Teacher Education Program, Majalengka University, 2024)
Critical thinking skills are essential for education and everyday life. Gender is an important component that affects students' critical thinking. However, we still lack an understanding of how gender, critical thinking, and learning strategies interact with each other. This study aims to analyse gender differences in critical thinking and evaluate how effective RADEC, PBL, and Direct Instruction learning models are in improving students' critical thinking skills. This research used experimental method with 3x2 factorial design. The sample of this study was 45 fourth grade elementary school students, consisting of 21 male students and 24 female students. The research data were collected through a critical thinking skills test consisting of ten essay questions that had been validated by experts. After the model was given to each group, then a test was given. To measure critical thinking skills. Two-way analysis of variance (Two Way Anova), assisted by SPSS IBM 29 for Windows, was used to analyse the research data using descriptive statistics and inferential statistics. The study found that gender differences affected students' critical thinking skills in learning Natural and Social Sciences (NSP). Female students obtained higher scores than male students. In addition, out of the other two learning models, the RADEC learning model is better in improving students' ability to think critically